ADOPSI KONSEP GATEKEEPER DALAM UNITED MODEL LEGISLATION ON MONEY LAUNDERING AND FINANCING TERRORISM TERHADAP UNDANG-UNDANG NOMOR 8 TAHUN 2010 TENTANG PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG - Rahmat Dwi Putranto; Fachry Hasani Habib (Fakultas Hukum Universitas Gadjah Mada, 2014)
AbstractThis study concentrates on how a professional could be considered as assistant in conducting money laundering in the matter of cutting-off the nexus between the assets in money laundering and its owner, and its role in preventing money laundering. Commonly, it is known as a gatekeeper. It has been stated in model legislation on money laundering and financing of terrorism for civil law country but not in Law Number 8 of 2010 in Indonesia. After researching on the urgency and comparison in other States there are some reasons about why Indonesia should adopt gatekeeper concept. One of them isthe fact of the existence of gatekeeper in current money laundering cases. IntisariPenelitian ini berpusat pada bagaimana profesi seseorang dapat menjadi bagian dari pencucian uang karena memutus aliran antara uang hasil pencucian uang dan pemiliknya dan juga keterlibatannya dalam pencegahan pencucian uang (gatekeeper). Ini telah diatur dalam model legislation on money laundering and financing of terrorism for civil law country tapi tidak dalam Undang Undang Nomor 8 Tahun 2010 tentang Pencegahan dan Pemberantasan Tindak Pidana Pencucian Uang.Fakta menunjukan gatekeeper sudah ada dibeberapa kasus pencucian uang.